Gambaran Pengetahuan Ibu Hamil Primigravida Tentang Anemia di Telaga Dewa Kota Bengkulu - Anisa Aurellia; Rina Delfina; Sardaniah (Pusat Riset dan Inovasi Nasional, 2026)
Anemia is the most common health problem in pregnancy. Physical changes that often occur are changes in blood circulation that can cause hemodilution. Anemia in pregnancy is one of the disorders in pregnancy, especially in developing countries. Primigravida pregnant women are based on the fact that they are a group that has not had previous pregnancy experience, so they have the potential to lack optimal information and education about anemia. The purpose of this study was to determine the knowledge of primigravida pregnant women about anemia in the Telaga Dewa Health Center Working Area, Bengkulu City. This type of research is descriptive with quantitative research design. The sampling method was accidental sampling technique with a sample of 60 primigravida pregnant women who were willing to be respondents. Data collection using a knowledge questionnaire instrument about pregnancy anemia. The results of this study showed more than half (55%) of respondents in the sufficient category, almost half (35%) of respondents in the less category, and a small proportion (10%) in the good category. This study shows that most respondents have sufficient knowledge about anemia.